Handling of allergen immunotherapy in the COVID‐19 pandemic: An ARIA‐EAACI statement. Issue 7 (11th July 2020) - Klimek, Ludger; Jutel, Marek; Akdis, Cezmi; Bousquet, Jean; Akdis, Mübeccel; Bachert, Claus; Agache, Ioana; Ansotegui, Ignacio; Bedbrook, Anna; Bosnic‐Anticevich, Sinthia; Canonica, Giorgio W.; Chivato, Tomas; et al.
Abstract :